Effect of Roux-en-Y gastric bypass in the control of erosive esophagitis - Albuquerque, Antônio Benincá; Rovani, André Luca Boeira; Puhl, Bruna Schmitt; Giacometti, Carlos Roberto; da Silva, Eduardo Dombroski; Jablonski, Elisa Estivalete; Carlotto, Fernanda Marcante; Burtet, Fernanda Tisott; da Silva, Jaline Ribeiro; Belke, Larissa; et al. (Clinical and Biomedical Research, 2019)
Background: Gastroesophageal reflux disease (GERD) is a multifactorial disease associated with environmental and genetic factors. Obesity is among the risk factors for its development, which also correlates with an increase in severity of clinical presentation and a higher incidence of complications associated with reflux. Aims: To evaluate the impact of Roux-en-Y gastric bypass on the control of erosive esophagitis and metabolic and anthropometric parameters related to obesity. Methods: This historical cohort study included a sample of 249 patients who had undergone bariatric surgery using the Roux-en-Y gastric bypass technique at the Hospital São Vicente de Paulo, Passo Fundo, southern Brazil, from January 2014 to December 2015. Results: Of 249 patients, 77.9% (190 patients) were female and the mean age was 38 years. The occurrence of reflux esophagitis was 81.1% (196 patients) in the preoperative period and 31.3% (75 patients) in the postoperative period. With regard to bariatric treatment response to control moderate and severe esophagitis (grades B, C and D), there was a reduction in prevalence from 62 (25%) to 12 (5%) patients (p<0.05). Conclusion: Bariatric surgery using the Roux-en-Y gastric bypass technique is effective in the control of reflux esophagitis. Regression is observed mainly in cases of moderate and severe esophagitis. Keywords: Erosive esophagitis; GERD; bariatric surgery; obesity; comorbidity